(untitled) (Clinics, 2015)
OBJECTIVE: The purposes of this study were to determine the coexistence of mastalgia and fibromyalgia, to investigate the effects of this combination on pain patterns, and to discuss the status of breast pain in the diagnostic algorithm of fibromyalgia syndrome. METHODS: Sixty-one female patients reporting breast pain during the last three months and 53 female patients diagnosed with fibromyalgia syndrome were enrolled in this study. The Breast Pain Questionnaire was administered to all participants in the mastalgia group and to those in the fibromyalgia syndrome group who had experienced mastalgia during the past three months. The patients in the fibromyalgia syndrome group were evaluated using the 2010 preliminary American College of Rheumatology classification criteria. All of the patients in the mastalgia group were evaluated for the diagnosis of fibromyalgia syndrome by a single physiatrist. The coexistence and pain patterns of mastalgia and fibromyalgia were assessed statistically. RESULTS: Approximately half of the patients with fibromyalgia syndrome (47.2%) reported having mastalgia at the time of admission and 37.7% of the patients with mastalgia met the diagnostic criteria for fibromyalgia syndrome. The patients with mastalgia in the fibromyalgia syndrome group had significantly higher total breast pain scores compared with the women in the mastalgia group. In addition, the patients with fibromyalgia syndrome in the mastalgia group had significantly higher Widespread Pain Index and Symptom Severity Scale scores than the patients with fibromyalgia syndrome. CONCLUSIONS: We suggest that mastalgia can be an aspect of the central sensitivity syndrome and can be added to the somatic symptoms of fibromyalgia.